2015
DOI: 10.1016/j.drugalcdep.2015.02.023
|View full text |Cite
|
Sign up to set email alerts
|

Promethazine use among chronic pain patients

Abstract: Background Concomitant use of opioids and promethazine has been reported in various subpopulations, including methadone maintenance patients, injection drug users, and at-risk teenagers. Promethazine is thought to potentiate the “high” from opioids. However, to date, the prevalence of promethazine use has not been determined among patients prescribed opioids for chronic pain. Methods Urine samples from 921 patients prescribed opioids for chronic pain were analyzed for promethazine. Demographic data, toxicolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 29 publications
1
24
1
Order By: Relevance
“…While there have been reports of nonmedical use of promethazine in combination with opioids from the US [23, 24], India [44], Vietnam [45], and Nepal [46], this, as well as nonmedical use of other prescription antihistamines (hydroxyzine and alimemazine), was uncommon in the present study, in combination with opioids or by itself. However, lifetime medical use of prescription antihistamines was high, reflecting that these drugs are commonly prescribed in Swedish medical care.…”
Section: Discussioncontrasting
confidence: 58%
See 1 more Smart Citation
“…While there have been reports of nonmedical use of promethazine in combination with opioids from the US [23, 24], India [44], Vietnam [45], and Nepal [46], this, as well as nonmedical use of other prescription antihistamines (hydroxyzine and alimemazine), was uncommon in the present study, in combination with opioids or by itself. However, lifetime medical use of prescription antihistamines was high, reflecting that these drugs are commonly prescribed in Swedish medical care.…”
Section: Discussioncontrasting
confidence: 58%
“…Recent US studies have indicated that the prescription drug promethazine—an antihistamine which is often used to treat anxiety and sleep disorders (Sandoz Inc., 2006)—might also have a misuse potential among persons with opioid dependence [23], as well as among chronic pain patients [24] and in the general population [25]. The study by Shapiro et al [23] investigated couse of promethazine and opioids and showed that 26% of patients in MMT had tested positive for promethazine, while only 15% of these had a valid prescription.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to substitution, use may also occur in a complementary fashion, such as using a second drug as a way to augment the effects of a primary drug. For example, a case study of pain clinic patients reported that promethazine can augment the feelings of euphoria among those using prescription pain reliever products (Lynch et al, 2015). Substances that are ingested by the same person can have markedly different effects depending upon their pharmacokinetics, absorption and distribution throughout the body (FDA, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, some currently available antiemetics appear to have abuse liability, for example, the antihistamine cyclizine, likely due to its stimulant effects . Moreover, the antihistamine promethazine and NK‐1 receptor antagonist aprepitant have both been reported to potentiate the euphoric effects of opioids, increasing the likelihood of misuse. Therefore, the availability of an experimental subject in which the effects of a candidate antiemetic could be examined concurrently with assessments of cognitive disruption and abuse liability could accelerate the discovery of new pharmacotherapies that are both effective and have a reduced side‐effect profile.…”
Section: Discussionmentioning
confidence: 99%